"So we start from zero": Lessons and reflections from online preschool during the COVID-19 pandemic. (December 2022) - Negrette, Giselle Martinez; Laixely, Jadyn; Cordoba, Tanya Espinosa; Sanders-Smith, Stephanie C
In the world of teacher education, the ability of teachers to adapt is associated with effective teaching. In the midst of a worldwide pandemic, however, teachers' adaptability was put to the ultimate test. With this in mind, this article explores the journey of two preschool teachers as they embarked on the sudden move from face-to-face to online instruction alongside school administrators, parents, and young children during the COVID-19 pandemic. Using a tripartite model of adaptability, the authors examine the cognitive, emotional and behavioral adaptations employed by the focal teachers, as they supported the learning process in a multilingual and multicultural early childhood program under unprecedented teaching conditions. The article highlights the lessons learned during this traumatic time and the innovative ways educators partnered with families to develop new means of collaboration. The paper ends by calling attention to the socioeconomic line of division that exists among various populations both locally and globally, which shapes the educational landscape in significant ways.